Leveraging shotgun proteomics for optimised interpretation of data-independent acquisition data: identification of diagnostic biomarkers for paediatric tuberculosis - Ehlers, Ashley (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScMedSc)--Stellenbosch University, 2020.